Reproduction of the human relevant potency threshold (HRPT) for estrogen receptor alpha agonism in an inference performance screen for ICCVAM’s regulatory scientific confidence framework - Ryman, Jessica; Becker, Richard A. (Frontiers in Toxicology, 2025)
Scientific confidence frameworks (SCFs) are alternatives to traditional validation for new approach methodologies (NAMs). The SCFs adapted by the Interagency Coordinating Committee for the Validation of Alternative Methods (ICCVAM) and the American Chemistry Council (ACC) both address inference performance—the ability of NAMs to predict or inform the biological effect of interest. Inference performance is a distinct evaluation procedure in ACC’s SCF but is blended into several steps of ICCVAM’s SCF. Here, we first reproduce the previously derived human relevant potency threshold (HRPT) for the estrogen receptor alpha (ERα) agonism of Borgert et al. (2018) using guideline and guideline-like studies; we found that a HRPT of 1 to 10–1 positively and consistently predicted clinical endometrial and endocervical effects. We next mapped inference performance to ICCVAM’s SCF and found that it can be used as an effective initial screen prior to performing more detailed characterizations in their SCF. We first conclude that a HRPT for ERα agonism of 10–2 to 10–4 is a health-protective NAM based on an established mode of action that could potentially be used in early screening, much like the threshold of toxicological concern. We then conclude that inference performance is a core requirement for SCFs.